A self-supported FeNi layered double hydroxide anode with high activity and long-term stability for efficient oxygen evolution reaction. Issue 12 (26th May 2021) - Su, Mingyu; Zhu, Shengli; Cui, Zhenduo; Li, Zhaoyang; Wu, Shuilin; Guo, Meiqing; Jiang, Hui; Liang, Yanqin
Abstract : The FeNi-layered double hydroxides nanoparticles with high oxygen evolution reaction activity and prominent catalytic lifetime were first self-assembled on FeNi foam. This catalyst has a promising future for large-scale non-precious materials in the industry. Abstract : Layered double hydroxides (LDHs) as highly efficient high oxygen evolution reaction (OER) catalysts have attracted significant attention owing to their high surface-to-bulk ratios, controllably layered structure, and tunable metal compositions. The unique lamellar architectures of FeNi-layered double hydroxide nanoparticles (FeNi-LDHs NPs) with OER activity and a prominent catalytic lifetime were first self-assembled on FeNi foam by a chemical corrosion engineering method. The obtained FeNi-LDHs@FeNi foam (FNF)-2 catalysts composed of FeNi hydroxides without any trace of NiO x species can function as active sites for an efficient OER. Moreover, considering the unique lamellar feature and partial crystallinity of FeNi hydroxides, FeNi-LDHs@FNF-2 can achieve a good balance between available active sites and electronic conductivity, thus endowing it with excellent oxygen evolution activity. This study affords an effective strategy to achieve optimized OER performance with a promising future for larger-scale non-precious materials in industry.